Pregnancy and maternal outcomes based on adherence to the current maternal weight gain recommendations for pregnant women with obesity - Hatch, Kimberly (My University, 2025)
BACKGROUND AND PURPOSE: Pre-pregnancy obesity increases the risk of gestational complications and affects 30% of pregnancies in the U.S. The current pregnancy weight gain recommendations for women with obesity are based on limited and somewhat conflicting data. The purpose of this study was to investigate whether adherence to current pregnancy weight gain recommendations is associated with the best birth and maternal outcomes among women with obesity. METHOD: Kansas Department of Health and Environment summary tables for certificates of live births for mothers with a BMI > 30 for years 2014-2019 were analyzed. Weight gain was classified as 1) less than recommended, 2) recommended, or 3) more than recommended. Birth outcomes, maternal outcomes, and delivery method were compared using relative risk (RR) with 95% confidence intervals (CI). RESULTS/FINDINGS: The majority (54.8%) of mothers with obesity gained more weight than recommended. Compared to the recommended weight gain, gaining more than recommended decreased the risk of low birth weight (RR 0.66; 95% CI 0.61-0.72), increased risk of hypertension (RR 1.32; 95% CI 1.29-1.40), and increased risk of cesarean birth (RR 1.07; 95% CI 1.05-1.10). Compared to the recommended weight gain, gaining less than recommended was associated with increased risk of low birth weight (RR 1.35; 95% CI 1.24-1.47), decreased risk of hypertension (RR 0.90; 95% CI 0.83-0.97), and decreased risk of cesarean birth (RR 0.95; 95% CI 0.92-0.98). CONCLUSION: Gestational weight gain above recommended values was common and increased the risk of gestational hypertension and cesarean birth but also decreased the risk of low birth weight.
Keywords: Pregnancy; Obesity; Gestational weight gain